Review: Increased Oral Bioavailability of Atorvastatin Calcium With Various Encapsulation Methods - Murad, Nabil Arvel (Universitas Padjadjaran (Unpad), 2023)
Atorvastatin calcium is statin class dyslipidemia drug which belongs to the class 2 bioclassification system (BCS) drug, namely drugs that have high permeability and low water solubility. Low solubility in water makes atorvastatin calcium also has low bioavailability (12%). Encapsulation method as a drug delivery system enable bioavailability enhancement of a drug. The aim of this literature review is to discover encapsulation method that can enhance oral bioavailability of atorvastatin calcium in recent research and to explain how obtained encapsulation method could enhance the bioavailability of atorvastatin calcium. The obtained research article from PubMed database. Several forms of encapsulation showed an enhancement in bioavailability, namely nanoparticles, and nanocrystals, nanosponges, nano lipid carrier (NLC), micro and nanoemulsions, and inclusion complexes. The highest increase in oral bioavailability of atorvastatin calcium was obtained by the formation of nanosponges using β-cyclodextrin material with the condensation-polymerization preparation method succeeded in increasing oral bioavailability by 14 times when compared to pure calcium atorvastatin formulations.Keywords: Atorvastatin calcium, Bioavailability, Encapsulation